Calcium phosphate ceramics prepared from natural waste materials - Toibah, Abd Rahim; Fatimah, Misran; Siti Sainillah, Sulaiman; Mohammad Ikmal, Mohamed; Mazlin, Mahamod; Azizah, Shaaban (2012)
Calcium phosphate bio-ceramics have widely been developed in biomedical applications due to their excellent biocompatibility, bioactivity and osteoconduction characteristics. These materials may be employed in many ceramic t(irms such as porous blocks, dense body, granular forms and hybrid composites to fill bone defects or voids. The main component of calcium phosphate ceramics is calcium. One of the means to produce calcium phosphate is by extracting it from natural sources such as eggshells. animal bones, cockles and coral as biogenic materials that are naturally available. Finer particles of the resulting powder promises better bioactivity and mechanical properties of bio-ceramic materials. This present research aims to synthesize calcium phosphate powders from raw materials, such as egg shell and bovine bone. The chemical and morphological properties of the materials arc studied and the phase stability and mechanical characteristics of the resulting granulated bin-ceramic material arc evaluated. The final products arc porous bioceramics used as ceramic scafi()lds for spongy bone application and dense ceramics used for load bearing applications.